2021
DOI: 10.1017/s095457942000214x
|View full text |Cite
|
Sign up to set email alerts
|

Family Minds: A randomized controlled trial of a group intervention to improve foster parents’ reflective functioning

Abstract: Family Minds is a brief group psychoeducational parenting intervention designed to increase the reflective functioning (RF) and mentalization skills of foster parents. RF is important for foster parents who have to build relationships with children whose adverse experiences increase their risk for psychosocial challenges. A randomized controlled trial (RCT) for Family Minds was conducted in Texas with 89 foster parents. The main aims of this study were to examine whether the intervention could significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 86 publications
1
30
0
1
Order By: Relevance
“…For example, the intervention longest in duration, the Reflective Fostering Programme (Midgley et al, 2019), did not lead to a significant change in PRF, whereas the shortest programme, Family Minds (Adkins et al, 2018;Adkins et al, 2021;Bammens et al, 2015), found significant improvements in PRF in three studies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, the intervention longest in duration, the Reflective Fostering Programme (Midgley et al, 2019), did not lead to a significant change in PRF, whereas the shortest programme, Family Minds (Adkins et al, 2018;Adkins et al, 2021;Bammens et al, 2015), found significant improvements in PRF in three studies.…”
Section: Discussionmentioning
confidence: 96%
“…2017) was used in three studies. In two of the studies evaluating the Family Minds programme for foster carers significant differences in PRF were found between the intervention and control groups with large effect sizes (Adkins et al, 2018;Adkins et al, 2021). Midgley at al.…”
Section: Reflective Functioning Outcomesmentioning
confidence: 99%
“…Accordingly, it would be necessary to adjust the interval and frequency of post-treatment follow-ups to determine whether and how the changes in both constructs are related to each other. For more frequent follow-up assessments, new instruments developed for less time-consuming PRF assessments could be helpful, such as the Mini-PRFI described earlier or the Reflective Functioning Five Minute Speech Sample that is currently being validated ( Adkins et al, 2021 ). Moreover, the difference in the rate of change could also apply to the self-focused and child-focused dimensions of PRF, especially since self-focused PRF contains complex reflections on mothers’ own negative emotional experiences that could be particularly difficult for high-risk mothers to access.…”
Section: Discussionmentioning
confidence: 99%
“…This issue of the contextual conditions of mental disorders was a foundation of psychoanalysis when Sigmund Freud developed his influential conceptual framework of the Oedipus conflict that, today of course, requires more subtle interpretations and clarifications. In psychoanalysis, the patient’s relationships with parents are a central theme of therapeutic reflection and intervention[ 90 ].…”
Section: Theories Of Addiction – From Psychoanalysis To the Stimulus-response Model To Psychoanalysis And The Ecological Perspectivementioning
confidence: 99%